2015
DOI: 10.1098/rspb.2015.1033
|View full text |Cite
|
Sign up to set email alerts
|

Structural mouthpart interaction evolved already in the earliest lineages of insects

Abstract: In butterflies, bees, flies and true bugs specific mouthparts are in close contact or even fused to enable piercing, sucking or sponging of particular food sources. The common phenomenon behind these mouthpart types is a complex composed of several consecutive mouthparts which structurally interact during food uptake. The single mouthparts are thus only functional in conjunction with other adjacent mouthparts, which is fundamentally different to biting-chewing. It is, however, unclear when structural mouthpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The other should concern the mouthparts. Although it has been suggested that especially insects represent extreme cases of evolutionary derived mouthparts ( Blanke et al , 2015 ), we should also expect strong modification representing true adaptations in cymothoiids. In an evolutionary framework those representatives of Cymothoidae should be most interesting as they are considered to represent less strongly derived forms.…”
Section: The Group Of Interest: Cymothoidaementioning
confidence: 84%
“…The other should concern the mouthparts. Although it has been suggested that especially insects represent extreme cases of evolutionary derived mouthparts ( Blanke et al , 2015 ), we should also expect strong modification representing true adaptations in cymothoiids. In an evolutionary framework those representatives of Cymothoidae should be most interesting as they are considered to represent less strongly derived forms.…”
Section: The Group Of Interest: Cymothoidaementioning
confidence: 84%
“…Further distal at the caudal side of the mandible, there is an impression into which a stud of the stipes fits. This stud can articulate with the mandible during the simultaneous mouthpart movement of the mandibles and maxillae (Blanke et al 2015b). Further disto-medial is a mandibular hump which articulates with parts of the endoskeleton (Hofmann 1908;Koch 2001).…”
Section: Collembolamentioning
confidence: 99%
“…obs) suggest more forceful adduction capabilities in Diplura compared to Collembola. As in Collembola, the dipluran mandible shows several interactions with parts of the gnathal pouch, endoskeletal elements, or parts of the maxilla which are currently debated regarding their homology (Koch 2000(Koch , 2001Blanke et al 2015b;Blanke and Machida 2015;Koch 2016). The proximal part of the mandible is formed like a pointed tip and fits into a sclerotized part of the gnathal pouch.…”
Section: Dipluramentioning
confidence: 99%
“…The acquisition of accurate three-dimensional (3D) morphological data is a crucial prerequisite for many taxonomic, functional, comparative and developmental studies (Jones et al 2009;Akkari et al 2015;Blanke et al 2015;Parapar et al 2017;Schachner et al 2017). Micro-computed tomography (lCT) accordingly has developed into a standard technique in biology for capturing internal and external information in 3D (Holdsworth & Thornton, 2002).…”
Section: Introductionmentioning
confidence: 99%